(untitled) (Bangladesh Journal of Microbiology, 2016)
In aquaculture, the incidence of bacterial resistance towards synthetic antibiotics has become a serious problem. Therefore, current research has been focused on detecting the presence of pathogenic bacteria in water bodies and finding a novel therapy against pathogens imparted by the natural products replacing the use of synthetic antibiotics. A total of 10 pond water samples were analysed to determine the pathogenic load employing conventional cultural and biochemical tests. Anti-bacterial activities of natural plants on fish pathogens were determined using the agar-well-diffusion method. All the water samples studied high heterotrophic bacteria counts, which were upto 109 cfu/ml. Among bacterial pathogens, Pseudomonas spp. and Vibrio spp. were found to be present in 6 samples and Aeromonas spp. in 2 samples. The in vitro anti-bacterial activity of the herbal plant extracts against the bacterial pathogens revealed that most of the plant extracts are effective against the pathogenic bacterial isolates. Bangladesh J Microbiol, Volume 31, Number 1-2,June-Dec 2014, pp 9-12